2020
DOI: 10.1016/j.mex.2020.101073
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible differentiation and characterization of neurons from mouse embryonic stem cells

Abstract: Investigation on the effects of disease-associated mutations on neurodevelopment is an essential approach to understand the molecular basis of neurological disorders and can be achieved by generating suitable animal models. However, some of the mutations preclude development of animal models, leaving cell-based models as the only options. Mouse embryonic stem cells (mESCs) are attractive because of the well-established technologies for introducing disease-associated mutations and the feasibility of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…The total loss of STAT3 in differentiated EBs is associated with a decrease of neuronal precursor cells [ 11 ]. In contrast to the study of Foshay et al, our data showed that NO 2 -OA treatment of EBs results in a significant increase of neuronal markers Nestin and Tubb3 (selected by [ 29 ]), and the presence of neurites was observed (see the morphology study for the details [ 25 ]). This discrepancy in the literature could be explained by the fact that NO 2 -OA inhibits the STAT3 phosphorylation at tyrosine 705 residue.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The total loss of STAT3 in differentiated EBs is associated with a decrease of neuronal precursor cells [ 11 ]. In contrast to the study of Foshay et al, our data showed that NO 2 -OA treatment of EBs results in a significant increase of neuronal markers Nestin and Tubb3 (selected by [ 29 ]), and the presence of neurites was observed (see the morphology study for the details [ 25 ]). This discrepancy in the literature could be explained by the fact that NO 2 -OA inhibits the STAT3 phosphorylation at tyrosine 705 residue.…”
Section: Discussioncontrasting
confidence: 99%
“…The gene expression of both neuro-specific markers was significantly up-regulated in NO 2 -OA-treated cells compared to both control and OA treatment at day 15 ( Figure 4 F–G). Neurogenisis was also evaluated using morphology studies, neurites were clearly visible at NO 2 -OA-treated cells at day 14 ( Figure 4 H; Figure S5 A,B) [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…One caveat to this proposed mechanism is the fact that neurons rely heavily on signaling feedback for complete differentiation. We found that low seeding density resulted in aberrant cell detachment, while others have shown that overcrowding of neuronal stem cell inhibits differentiation ( 29 ). As a differentiation-specific gene, SNCA expression would also be indirectly affected by seeding density.…”
Section: Discussionmentioning
confidence: 82%
“…S1A). To characterize the roles of circAcbd6 on NSC differentiation, we performed RT-qPCR and Western blot analysis of three neuronal markers, Map2, Neurod1, and ChAT (19)(20)(21). The results showed that Map2, Neurod1, and ChAT in LV-circAcbd6 group were upregulated significantly compared with LVnegative control (NC) group (Fig.…”
Section: Effects Of Circacbd6 Overexpression On Differentiation Of Nscsmentioning
confidence: 96%